Scaling-up biofortified beans high in iron and zinc through the school-feeding program: A sensory acceptance study with schoolchildren from two departments in southwest Colombia - Beintema, Joni J.S.; Gallego-Castillo, Sonia; Londoño Hernandez, Luis Fernando; Restrepo Manjarres, José; Talsma, Elise F. (Wiley, 2018)
Iron and zinc deficiencies are global health problems, affecting mostly pregnant women and young children. In 2016, biofortified iron and zinc beans were introduced in Colombia. The incorporation of biofortified beans into the national school‐feeding program could facilitate adoption and potentially improve the nutritional status of large populations. However, biofortified beans have to be accepted in order to be consumed by populations. We therefore studied the sensory acceptability of two biofortified beans, BIO‐101 and BIO‐107, and local beans at schools with free feeding services in two departments of southwest Colombia. Measured on a five‐point Likert scale, the mean overall scores were 3.88 ± 0.64, 3.79 ± 0.74, and 3.81 ± 0.76, for BIO‐101, BIO‐107, and the local bean varieties, respectively, without significant differences. The children in Piendamó (Cauca) slightly preferred BIO‐107 over the local bean (p < .05) based on color, smell, and taste. The children in Caicedonia (Valle del Cauca) slightly favored the local bean over BIO‐107 (p < .05), regarding size, smell, and taste. Overall acceptability in schoolchildren was good for all beans without significant differences. This study advocates incorporation of accepted biofortified beans in the school‐feeding program, in order to reach large groups of schoolchildren and potentially improve their nutritional statuses.